2019
DOI: 10.1016/j.ctcp.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness for people with long-term conditions and their family caregivers: A systematic review

Abstract: University for funding the project.• Loukia Gkanasouli for research assistance during the project.• Dr. Grace Poulter for support with academic writing. Competing interests statement:No conflict of interest has been declared by the authors. Funding statement:The review was funded by Glasgow Caledonian University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“… 67 69–71 Three reviews focused on caregivers of persons with dementia, 67 69 70 while one review took interest in caregivers of people with various illnesses. 71 Health-related outcomes varied and included: depression (n = 3), anxiety (n = 3), and cognition and biomarkers for stress (n = 1). Two reviews included meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 67 69–71 Three reviews focused on caregivers of persons with dementia, 67 69 70 while one review took interest in caregivers of people with various illnesses. 71 Health-related outcomes varied and included: depression (n = 3), anxiety (n = 3), and cognition and biomarkers for stress (n = 1). Two reviews included meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 69 70 Cheng et al 67 reported a significant positive effect on depression in grouped meta-analysis. Parkinson et al 71 reported mixed results, with interventions showing some positive changes in anxiety and depression scores, but with small and waning effects. While some authors acknowledged the importance of potential moderating factors and heterogeneity among caregivers, 70 71 there were no findings to report regarding this question.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to investigate online MBI with care partnerships experiencing anxiety and depression following stroke (Parkinson et al, 2019;Parkinson, 2021). The study uses mixed methods case study research and combines an initial quasi-experimental stage followed by IPA (Creswell & Plano Clark, 2017;Smith et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments with MBIs include using online technology, involving different clinical populations, and/or delivering MBI in care partnerships (Fish et al, 2016). This study is the first study to examine online MBI with care partnerships experiencing anxiety and depression symptoms following stroke (Parkinson et al, 2019;Parkinson, 2021).…”
Section: Mindfulness-based Interventions (Mbis)mentioning
confidence: 99%